Ekowisata Dalam Perspektif Pemberdayaan Masyarakat (Studi Masyarakat Pesisir Alor Nusa Tenggara Timur) - Abdul Malik Iskandar; Hasanuddin Kasim; Akhiruddin Akhiruddin; Jalal Jalal; Muhamad Ihsan Azhim (Universitas Negeri Makassar, 2022)
This study aims to examine and describe the from of community empowerment on ecotourism potential in the coastal tourism area, and the strategic impact of community empowerment on ecotourism potential in the coastal tourism area of Alor District in East Nusa Tenggara Province. This type of research uses descriptive qualitative research by determining the number of informants consisting of 10 informants selected by purposive sampling technique with the criteria of informants from the local government and the people living in Alor Regency. Data collection techniques used are observation, interviews, and documentation. The data analysis technique used by the researcher went through three stages of work, namely data reduction, data presentation, and drawing conclusions. Data validation techniques used were source triangulation and method triangulation. The results of the study show that 1) the from of community empowerment in ecotourism potential is by introducing and disseminating the concept of ecotourism openly to the community to foster an understanding of ecotourism from community empowerment it self, as well as marketing and tourism promotion by assisting tourism activities and business capital assistance, 2) the strategic impact of community empowerment on ecotourism potential in coastal tourism area, namely the socio-economic and cultural impact. Penelitian ini bertujuan untuk mengkaji dan mendeskripsikan bentuk pemberdayaan masyarakat pada potensi ekowisata di kawasan wisata pantai dan dampak strategis pemberdayaan masyarakat pada potensi ekowisata di kawasan wisata pantai Kabupaten Alor Provinsi Nusa Tenggara Timur. Jenis penelitian ini menggunakan penelitian deskriptif kualitatif dengan penentuan jumlah informan terdiri dari 10 informan yang dipilih dengan teknik purposive sampling dengan kriteria informan masyarakat pesisir dan pemerintah setempat di Kabupaten Alor. Teknik pengumpulan data yang digunakan adalah observasi, wawancara mendalam dan dokumentasi. Teknik analisis data yang digunakan peneliti melalui tiga tahapan kerja yakni reduksi data, penyajian data dan penarikan kesimpulan. Teknik pengabsahaan data yang digunakan yakni triangulasi sumber dan triangulasi metode. Hasil penelitian menunjukan bahwa 1) bentuk pemberdayaan masyarakat pada potensi ekowisata dengan memperkenalkan dan mensosialisasikan konsep ekowisata secara terbuka kepada masyarakat untuk menumbuhkan pemahaman tentang ekowisata dari pemberdayaan masyarakat itu sendiri, serta pemasaran dan promosi wisata dengan pendampingan kegiatan pariwisata dan bantuan modal usaha. 2) dampak strategis yang ditimbulkan dari pemberdayaan masyarakat pada potensi ekowisata di kawasan wisata pantai yakni dampak ekonomi, dan sosial budaya.